Model Bisnis Aspek Legal pada Keamanan Dokumen dan Data Pribadi E-Government - Missi Hikmatyar; Aso Sudiarjo; Hilma Lutfiani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Indonesia ranks 88th under other ASEAN countries such as Malaysia, Singapore, Thailand and Vietnam as countries that implement an Electronic-Based Government System (SPBE) or known as e-government. With the Covid 19 pandemic, the government service system was forced to switch to using the internet. However, Indonesia is not yet ready to implement e-government because several aspects include legal aspects of e-government. The legal aspects in question are document legality, personal data security in the use of e-government systems. Currently, Indonesia does not have a foundation to regulate these aspects, so that Indonesia has not been able to implement e-government as a government service, while with the COVID-19 pandemic, government services must switch to an electronic-based service system. Problems from various aspects can be overcome by conducting research with the target of a business model that can be used as a reference in the legality of documents, models and security of personal data. The research case study was conducted at the Tasikmalaya Government Office, West Java. The method used to build the model is the RACI chart to see the connectedness of stakeholders who play a role in the designed business model. Making a business model is made with a standard notation in making a business model, namely BPMN. The resulting model is a business model on document security and data privacy by utilizing the RSA algorithm and Qr-code scheme, and a business model for digital signatures.